Case report: a child with type 1 neurofibromatosis and intellectual disability - Elice Wijaya; Ni Luh Putu Ratih Vibriyanti Karna; Ida Ayu Uttari Priyadarshini (Bali Dermatology and Venereology Journal, 2021)
Background: Neurofibromatosis is a genetic disorder which manifests as a tumor that surrounds the nerves and several other pathologic presentations.Case: Female, 11 years old, according to history, physical examination and supporting investigation was consistent with the diagnostic criteria of type 1 neurofibromatosis (NF-1). Patient also has intellectual disability. On the patient, a tumor on the foot region that was functionally disabling was found and a surgical treatment was performed.Discussion: Cognitive disorder is the most common neurological complication in individuals with NF-1 and usually present with low intelligence quotient (IQ). There is no specific treatment to prevent the development of NF-1. However, early treatment can minimize and prevent further complication. Treatment for the patient involve multiple clinical discipline.Conclusion: A neurofibromatosis case can be diagnosed clinically alone, however, since there are many other systemic involvements that require multi-disciplinary approach.